2007
DOI: 10.1542/peds.2006-3037
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Persistent Pulmonary Hypertension of the Newborn

Abstract: Our findings suggest an increased risk for persistent pulmonary hypertension of the newborn associated with cesarean delivery; late preterm or postterm birth; being large for gestational age; and maternal black or Asian race, overweight, diabetes, and asthma. It remains unclear whether some of these factors are direct causes of persistent pulmonary hypertension of the newborn or simply share common causes with it; however, clinicians should be alert to the increased need for monitoring and intervention among p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
123
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 31 publications
15
123
4
2
Order By: Relevance
“…29 Those that were considered potential confounding factors in analyses of the relationships among analgesics and PPHN are presented in Table 2. Factors associated with increased risk of PPHN included maternal race/ethnicity (ie, Black or Asian), BMI .27, maternal diabetes mellitus or asthma, cesarean delivery, male infant gender, birth weight ,2500 or .4000 g, gestational age ,37 or .41 weeks, and large for gestational age designation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Those that were considered potential confounding factors in analyses of the relationships among analgesics and PPHN are presented in Table 2. Factors associated with increased risk of PPHN included maternal race/ethnicity (ie, Black or Asian), BMI .27, maternal diabetes mellitus or asthma, cesarean delivery, male infant gender, birth weight ,2500 or .4000 g, gestational age ,37 or .41 weeks, and large for gestational age designation.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 This method ensures more complete reporting 29,31 and allows linkage between all medications and occurrences of illnesses.…”
Section: Assessment Of Exposurementioning
confidence: 99%
“…60 Cesarean delivery, late preterm, large for gestation age and maternal asthma might be also important risk factors for PPHN. 61 Pathophysiological mechanisms of PPHN have been investigated at the level of endothelial as well as smooth muscle function. 59 Functional changes in PPHN are primarily correlated with endothelial dysfunction, resulting in an imbalance between vasodilation and vasoconstriction.…”
Section: Pphn and Enosmentioning
confidence: 99%
“…There are many studies which have found various risk factors associated with PPHN [2][3][4] which have been identified retrospectively. However there is paucity of data about the newborns who have one or more risk factors for PPHN and have some degrees of PAH not significant enough to cause hypoxemia and desaturation.…”
Section: Introductionmentioning
confidence: 99%